Phytochemical analysis, mineral composition and in vitro antioxidant activities of Solanum macrocarpon leaves - Usunobun, Usunomena; V. Chinwe, Igwe (International Journal of Health, 2016)
Background: The aim of this study is to determine phytochemicals and mineral composition as well as in vitro antioxidant activities of Solanum macrocarpon leaves.Methods: Qualitative phytochemical screening was carried out using standard procedures while Mineral analysis was carried out using Atomic Absorption Spectrophotometer (AAS). Solanum macrocarpon leaves were also subjected for measurement of reducing power and antioxidant/radical scavenging activity (2,2-Diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity).Results: Phytochemical screening revealed the presence of flavonoids, saponins, alkaloids etc. Mineral analysis showed calcium (256.60mg/100g) to be higher in concentration and copper (0.62mg/100g) least in concentration while manganese was absent. Other minerals includes magnesium (81.69mg/100g), potassium (87.22mg/100g), sodium (32.51mg/100g), iron (31.41mg/100g), zinc (1.41mg/100g). Solanum macrocarpon leaves showed maximum antioxidant activity (DPPH free radical scavenging and reducing power capacity) as the higher the concentration, the higher the antioxidant activity, thus the better the free radical scavenging potentials.Conclusion: The data from this study revealed that Solanum macrocarpon has a rich content of phytochemicals, namely, saponins, alkaloids, flavonoids as well as minerals, bioactive components that are associated with health impacts. This study also revealed that Solanum macrocarpon leaves exhibit antioxidant activity. These findings thus suggest that Solanum macrocarpon leaves could act as potent source of antioxidants.